Quercetin, a flavonoid antioxidant, modulates endothelium-derived nitric oxide bioavailability in diabetic rat aortas - Machha, A.; Achike, F.I.; Mustafa, A.M.; Mustafa, Mohd Rais (Elsevier, 2007)
The present work examined the eﬀect of chronic oral administration of quercetin, a ﬂavonoid antioxidant, on blood glucose, vascular function and oxidative stress in STZ-induced diabetic rats. Male Wistar-Kyoto (WKY) rats were randomized into euglycemic, untreated diabetic, vehicle (1% w/v methylcellulose)-treated diabetic, which served as control, or quercetin (10 mg kg 1 body weight)-treated diabetic groups and treated orally for 6 weeks. Quercetin treatment reduced blood glucose level in diabetic rats. Impaired relaxations to endothelium-dependent vasodilator acetylcholine (ACh) and enhanced vasoconstriction responses to a1-adrenoceptor agonist phenylephrine (PE) in diabetic rat aortic rings were restored to euglycemic levels by quercetin treatment. Pretreatment with N x -nitro-L-arginine methyl ester (L-NAME, 10 lM) or methylene blue (10 lM) completely blocked but indomethacin (10 lM) did not aﬀect relaxations to ACh in aortic rings from vehicle- or quercetin-treated diabetic rats. PE-induced vasoconstriction with an essentially similar magnitude in vehicle- or quercetin-treated diabetic rat aortic rings pretreated with L-NAME (10 lM) plus indomethacin (10 lM). Quercetin treatment reduced plasma malonaldehyde (MDA) plus 4-hydroxyalkenals (4-HNE) content as well as increased superoxide dismutase activity and total antioxidant capacity in diabetic rats. From the present study, it can be concluded that quercetin administration to diabetic rats restores vascular function, probably through enhancement in the bioavailability of endothelium-derived nitric oxide coupled to reduced blood glucose level and oxidative stress